Korelasi Antara Konsep Diri Sosial Dengan Hubungan Sosial - Asweni, Resti; Khairani, Khairani (Konselor, 2013)
The ability of young people in social relationships may be influenced by the concept of self-possession. The fact that there are shows still encountered students who have poor social relationships. This study aims to reveal how the correlation between social self-concept of students in the school of social relationships. Type shaped descriptive correlational study. The study population totaled 444 students, using proportional random sampling technique obtained a sample of 82 students. The results showed a significant correlation between social self-concept of social relations.Keyword: Social Self-concept; Social Relationships